Tackling Intermediate Students’ Fossilized Grammatical Errors in Speech Through Self-Evaluation and Self-Monitoring Strategies (2018)
The purpose of this action research study was to help English language intermediate students tackle fossilized grammatical errors in their speech, which were verb form, missing subject, and word choice. In order to do so, the researcher used visual input such as pictures and colored stickers for self-monitoring purposes, as well as self-evaluation charts for participants to follow up on their process; additionally, voice recordings and field notes were used to help the researcher keep track of students’ progress. Results showed that participants developed more awareness and attentiveness towards their fossilized mistakes which were reflected in the repairs they were able to make along the implementation process.